Directed Graphene‐Based Nanoplatforms for Hyperthermia: Overcoming Multiple Drug Resistance. Issue 35 (3rd August 2018) - Tu, Zhaoxu; Qiao, Haishi; Yan, Yuting; Guday, Guy; Chen, Wei; Adeli, Mohsen; Haag, Rainer
Abstract: Multidrug resistance (MDR), which leads tumors resistance to traditional anticancer drugs, can cause the failure of chemotherapy treatments. Herein, we present a new way to overcome this problem using smart multifunctional graphene‐based drug delivery systems which can target subcellular organelles and show synergistic hyperthermia and chemotherapy. Mitochondria‐targeting ligands are conjugated onto the doxorubicin‐loaded, polyglycerol‐covered nanographene sheets to actively accumulate them inside the mitochondria after charge‐mediated cellular internalization. Upon near‐infrared (NIR) irradiation, adenosine triphosphate (ATP) synthesis and mitochondrial function were inhibited and doxorubicin released into the cellular interior. The hyperthermia‐accelerated drug release led to a highly selective anticancer efficiency, confirmed by in vitro and in vivo experiments. Abstract : Multiple functionalized graphene nanosheets accumulate in mitochondria after cellular uptake, disrupting mitochondrial function upon laser irradiation and resulting in more of the released Doxorubicin (DOX) being delivered into the nucleus. These multiple functionalized graphene sheets could overcome multidrug resistance and achieve effective synergistic tumor therapy. hPG=hyperbranched polyglycerol.